A Rare Coexistence of Paraneoplastic Cerebellar Degeneration: Papillary Thyroid Carcinoma - Ayas, Zeynep Özözen (Curr Oncol, 2021)
Paraneoplastic cerebellar degeneration (PCD) is a rare neuroimmunological disease that may accompany tumors. In this article, we present a patient with progressive gait difficulty who was diagnosed with PCD and, in a rare comorbidity, with papillary thyroid carcinoma (PTC) following malignancy screening. A 46-year-old male patient reported having experienced poor balance for 2 years. A neurological examination revealed nystagmus, intention tremor, and ataxia, and anti-thyroid peroxidase and anti-thyroglobulin levels were found to be elevated. A brain MRI showed significant cerebellar atrophy in the superior vermis. Malignancy screening for PCD was performed, and thyroid ultrasonography revealed a nodule in the left lobe, while PET/CT detected elevated focal F-18 fluorodeoxyglucose uptake in the thyroid. Onconeuronal antibodies (anti-Hu, anti-Yo, anti-Ri, anti-amphiphysin, anti-Tr, anti-PPCA-2, anti-Ma, anti-CV-1, and anti-ANNA-3) were negative. Pathologic examination of the thyroid revealed PTC, for which the patient was treated with 0.4 g/kg intravenous immunoglobulin and referred to the medical oncology department. This case demonstrates that clinicians must be alert to the rare comorbidity of PCD and PTC.